Role of customised negative-pressure wound therapy in the integration of split-thickness skin grafts: A randomised control study - Mir Mohsin; Haroon Rashid Zargar; Adil Hafeez Wani; Mohammad Inam Zaroo; Peerzada Umar Farooq Baba; Sheikh Adil Bashir; Altaf Rasool; Akram Hussain Bijli (Indian Journal of Plastic Surgery)
Background: Split-thickness skin grafting (STSG) is a time-tested technique in wound cover, but many factors lead to suboptimal graft take. Role of custom-made negative-pressure wound therapy (NPWT) is compared with conventional dress in the integration of STSG and its cost is compared with widely used commercially available NPWT. Materials and Methods: This is a parallel group randomised control study. Block randomisation of 100 patients into one of the two groups (NPWT vs. non-NPWT; 50 patients each) was done. Graft take/loss, length of hospital stay post-grafting, need for regrafting and cost of custom-made negative pressure wound therapy (NPWT) dressings as compared to widely used commercially available NPWT were assessed. Results: Mean graft take in the NPWT group was 99.74% ± 0.73% compared to 88.52% ± 9.47% in the non-NPWT group (P = 0.004). None of the patients in the NPWT group required second coverage procedure as opposed to six cases in the non-NPWT group (P = 0.035). All the patients in the NPWT group were discharged within 4–9 days from the day of grafting. No major complication was encountered with the use of custom-made NPWT. Custom-made NPWT dressings were found to be 22 times cheaper than the widely used commercially available NPWT. Conclusions: Custom-made NPWT is a safe, simple and effective technique in the integration of STSG as compared to the conventional dressings. We have been able to reduce the financial burden on the patients as well as the hospital significantly while achieving results at par with other studies which have used commercially available NPWT.